2014
DOI: 10.1016/j.socscimed.2014.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of stigma and discrimination of people with schizophrenia in India

Abstract: Stigma contributes greatly to the burden of schizophrenia and is a major obstacle to recovery, yet, little is known about the subjective experiences of those directly affected in low and middle income countries. This paper aims to describe the experiences of stigma and discrimination of people living with schizophrenia (PLS) in three sites in India and to identify factors influencing negative discrimination.The study used mixed methods and was nested in a randomised controlled trial of community care for schiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(143 citation statements)
references
References 35 publications
9
128
2
4
Order By: Relevance
“…Findings on the experiences of stigma of PLS taking part in this study have been reported previously in this journal (Koschorke et al., 2014). The aim of the present paper is to describe caregivers’ own experiences of stigma, and the factors influencing these experiences in India.…”
Section: Introductionsupporting
confidence: 78%
“…Findings on the experiences of stigma of PLS taking part in this study have been reported previously in this journal (Koschorke et al., 2014). The aim of the present paper is to describe caregivers’ own experiences of stigma, and the factors influencing these experiences in India.…”
Section: Introductionsupporting
confidence: 78%
“…On the other hand, some smaller studies suggest stark differences between HIC and LAMIC settings, e.g., studies from China (Chung & Wong, 2004) and India (Koschorke et al 2014), with rates of experienced discrimination much lower than those commonly reported from HIC studies, and qualitative differences in the meaning and appraisal of the experiences made. At first sight, this appears to support the findings of early cross-cultural research on stigma suggesting that the stigma of mental illness may be less marked in nonindustrialised societies due to a more supportive environment with more social cohesion and therefore less risk of prolonged rejection, isolation, segregation and institutionalisation (Askenasy, 1974;Cooper & Sartorius, 1977;El-Islam, 1979;Waxler, 1979) cited in (Littlewood, 1998) The better prognosis of schizophrenia found in international studies by the World Health Organization (WHO, 1979;Jablensky et al 1992;Harrison et al 2001;Hopper et al 2007) has therefore commonly been attributed to less stigmatisation in LAMIC (Rosen, 2003).…”
Section: Global Patterns Of Stigma and Discriminationmentioning
confidence: 94%
“…Socio-economic factors, such as poverty and access to healthcare, have long been found to be associated with outcomes of mental illness (Lund et al 2011) and determine the context in which stigma is enacted and experienced (Switaj et al 2009;Thornicroft et al 2009;Livingston & Boyd, 2010;Evans-Lacko et al 2013). In India and other LAMICs, where most people with mental illness do not have access to social welfare benefits, the negative economic consequences of stigma, e.g., through discrimination in work, may be so severe as to threaten the economic survival of entire families (Koschorke et al 2014).…”
Section: Context-specific Factors Relevant To Stigma and Discriminatimentioning
confidence: 99%
“…Penelitian Koschorke et al (2014) menyatakan bahwa caregiver memiliki stigma yang tinggi selama merawat klien skizofrenia. Akibatnya caregiver sering mendapatkan reaksi yang negatif dari orang lain karena gejala yang dimunculkan oleh klien skizofrenia seperti kritikan dan diskriminasi.…”
Section: Beban Sosialunclassified
“…Penolakan yang dilakukan oleh caregiver terkait dengan buruknya image masyarakat tentang penyakit skizofrenia. Penolakan yang dilakukan oleh caregiver mengakibatkan caregiver sering menyembunyikan atau bahkan tidak mengakui klien sebagai anggota keluarganya (Koschorke et al, 2014;Yin et al, 2014). Penelitian Rammohan & Rao (2002) menjelaskan bahwa beberapa caregiver sering menggunakan strategi koping negatif pada periode awal yaitu denial atau menolak.…”
Section: Strategi Koping Yang Digunakanunclassified